Correspondence Between Objective and Self-reported Endocrine Therapy Adherence Among Women With Breast Cancer. Issue 9 (27th December 2018) - Bright, Emma E; Stanton, Annette L
Abstract: Background: Among the approximately 70% of women with hormone receptor-positive breast cancer, endocrine therapies lower the likelihood of recurrence. Nonadherence to endocrine therapy predicts lower survival. Purpose: We examined concordance between self-reported and objective indicators of adherence and predictors of over-reporting endocrine therapy adherence among survivors of breast cancer. Methods: Women with breast cancer ( N = 112) receiving their initial endocrine therapy prescription completed three assessments at prescription initiation (Time 1), 1 month (Time 2), and 4 months later (Time 3). At Time 1, participants were provided a medication event monitoring system (MEMS) cap to assess adherence; it was collected at Time 3. Women completed items regarding self-reported adherence, depressive symptoms, cancer-related coping processes, and the patient–physician relationship. Results: MEMS was significantly negatively correlated with the self-reported nonadherence measurements of occasionally forgetting (Time 2, ρ = −.29, p < .01; Time 3, ρ = −.24, p < .01), nonadherence in the past week (Time 2, ρ = −.53, p < .01; Time 3, ρ = −.45, p < .01), and nonadherence in an average week in the past month (Time 2, ρ = −.38, p < .01; Time 3, ρ = −.39, p < .01). Concordance in objective and self-reported adherence measures was evident in 83% of women at Time 2 and 73% at Time 3. Older age was significantly associated ( p < .01) with discordance. Conclusions: Findings reveal moderate correspondence between objective and self-report measures, with self-report overestimating objective adherence. Clinicians should be aware when treating older breast cancer survivors that they are more likely to over self-report their endocrine therapy adherence. Abstract : Among women with breast cancer, self-reported measures overestimate adherence to endocrine therapy (i.e., hormone therapy which stops or slows the growth of cancer) in comparison to electronic monitoring systems.